All-regime two-phase flow modeling using a novel four-field large interface simulation approach. (December 2021) - Frederix, E.M.A.; Dovizio, D.; Mathur, A.; Komen, E.M.J.
Abstract: Two-phase flows may occur in many regimes, ranging from dispersed flow, slug or plug flow to stratified flow. To capture all those regimes with a monolithic approach, a so-called all-regime two-phase model should be developed. This paper presents such an all-regime two-phase modeling approach called Four-Field Large Interface Simulation (FF-LIS), in which we consistently consider two phases (gas and liquid) which can both be either resolved or sub-grid, resulting in four fields. The efficacy of this approach hinges on the accuracy with which the inter-scale mass, momentum and energy transfer terms between dispersed and resolved regimes are captured. In this paper, we introduce three phenomenological mechanisms to control the inter-scale transfer: absorption, break-up and coalescence. The separation of multiphase scales allows for the explicit modeling of transfer between them, whereas other methods often rely on an algebraic regime map in which transfer between scales is accounted for implicitly. We apply FF-LIS to the simulation of both bubbly and fully resolved single bubble flow, as a way of validating FF-LIS in those two two-phase limits. Next, the transfer terms are illustrated by simulation of bubbles rising in a column. As the bubble concentration increases, it is shown that a transfer from sub-grid to resolved occurs. Finally, we apply FF-LIS to the simulation of two-phase horizontal pipe flow in which the several flow regimes, depending on the superficial velocities, are recovered, and to the simulation of a plunging jet in which FF-LIS is shown to produce an entrained bubble plume. FF-LIS presents a computational platform for faithful two-phase resolved and sub-grid simulation of relevant real-world two-phase problems, and allows two-phase modelers for the explicit control on what can be resolved, and what should be sub-grid. Highlights: A novel all regime two-phase model is developed. The model uses four fields to distinguish between scales (dispersed & continuous) and phase (liquid & gas). This allows explicit modeling of inter-scale transfers. The model is successfully validated in simple cases and applied to more integral test cases.